1994
DOI: 10.1097/00000658-199406000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Endogenous Cytokines in Chronic Wounds

Abstract: This new technique appears useful for measuring endogenous levels of cytokines. Levels of cytokines found in these chronic wounds are much lower than those reported from acute wounds. The marked variation found among the 20 wounds may help to explain the differences reported in recent wound healing trials with exogenous cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
121
0
4

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(126 citation statements)
references
References 9 publications
1
121
0
4
Order By: Relevance
“…A recent study that analyzed acute human wound fluid also found predominantly PDGF-AA (12). Another study in which wound fluid from chronic pressure ulcers was analyzed found variable amounts of PDGF present, but the assay was unable to discriminate among the isoforms (49). Recently, Ansel and co-workers (47) identified PDGF-AA in provisional matrix within experimental human wounds.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that analyzed acute human wound fluid also found predominantly PDGF-AA (12). Another study in which wound fluid from chronic pressure ulcers was analyzed found variable amounts of PDGF present, but the assay was unable to discriminate among the isoforms (49). Recently, Ansel and co-workers (47) identified PDGF-AA in provisional matrix within experimental human wounds.…”
Section: Discussionmentioning
confidence: 99%
“…In preliminary experiments with defined amounts of proteins, a recovery of 88-98% was described when extracting the beads with equal volumes of phosphate buffered saline for 12 hours (Cooper et al 1994).…”
Section: Sampling Of Chronic Wound Fluidsmentioning
confidence: 99%
“…In a small study published in 1993, Lev-Ran and Hwang (11) reported an elevation of PDGF and EGF in the plasma of diabetic subjects compared with control subjects. However, Cooper et al (12) showed that a number of growth factors were markedly reduced in wound fluid from chronic wounds compared with acute wounds. Bennett and Schultz (13) postulated increased destruction or inhibition of growth factors by elevated levels of proinflammatory cytokines and metallomatrix protein following repeated trauma and infection.…”
mentioning
confidence: 99%